Acácia da Amazônia No. 7’s Masonic Lodge role in Education in Colinas do Tocantins - Ramalho, Emmanuel (2025)
This paper aims to investigate the history of the work of a Masonic lodge, Acácia da Amazônia No. 7, in education in Colinas do Tocantins. The research is based on bibliographical and documentary methodology and semi-structured interview. The research identified that the lodge created and maintained a technical education foundation for vulnerable children and adolescents and that its philanthropic work in the municipality's education ceased when access to public education became sufficient for the population.